Efektivitas Klausul Pilihan Penyelesaian Sengketa dalam Perjanjian Joint Venture di Indonesia - Kesumadianty, Arnelia (LPPM Institut Pendidikan Nusantara Global, 2025)
Joint ventures (JVs) have become one of the most widely used instruments for Indonesian companies, both private and state-owned enterprises, to expand their business, establish strategic alliances, and gain access to international markets, technology, and capital. In addition to driving commercial growth, JVs also play a significant role in supporting national agendas such as industrial downstreaming, energy transition, and digital transformation. Despite their substantial potential, JVs often face considerable legal and operational challenges. Disputes may arise at various stages, including the formation, execution, and termination of the JV, often due to differences in business culture, vague contractual provisions, governance issues, or diverging interests between parties. In cross-border contexts, these disputes are further complicated by differing legal systems and regulatory environments, making arbitration an essential and effective mechanism for dispute resolution. This paper aims to examine how JVs can be strategically managed to avoid common errors, reduce legal uncertainty, and ensure smooth cooperation between partners. It emphasizes the importance of drafting clear, comprehensive, and enforceable JV agreements that include well-defined dispute resolution clauses. By integrating preventive legal strategies and choosing arbitration as a neutral and efficient forum for resolving conflicts, companies can not only safeguard their investments but also foster long-term, stable partnerships with international collaborators.